Gallucci's Commentary on Dürer’s 'Four Books on Human Proportion' - Hutson, James (Open Book Publishers, 2021)
"In 1591, Giovanni Paolo Gallucci published his Della simmetria dei corpi humani, an Italian translation of Albrecht Dürer’s Four Books on Human Proportion. While Dürer’s treatise had been translated earlier in the sixteenth-century into French and Latin, it was Gallucci’s Italian translation that endured in popularity as the most cited version of the text in later Baroque treatises, covering topics that were seen as central to arts education, connoisseurship, patronage, and the wider appreciation of the studia humanitatis in general.